2015
DOI: 10.1519/jsc.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Peristaltic Pneumatic Compression on Repeated Anaerobic Exercise Performance and Blood Lactate Clearance

Abstract: External pneumatic compression (EPC) use in athletics is increasing. However, there is a paucity of evidence supporting the effectiveness of EPC in aiding recovery and performance. We sought to determine the efficacy of EPC for acute recovery of anaerobic power and lactate clearance following a fatigue protocol. Fourteen (n = 14; women = 7 and men = 7), apparently healthy, active subjects (aged 22.73 ± 4.05 years) were enrolled in this randomized crossover design study. After familiarization sessions, subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 16 publications
4
47
1
4
Order By: Relevance
“…The NMES groups in the present study was administered a low frequency electrical stimulation during the recovery period showed a significant recovery of blood lactate and anaerobic performance as compared to control group, which is similar to the results found in previous studies [21,24,26,27,30,[38][39][40][41], although some studies have also reported contrasting findings [21,[42][43][44]. IFT used produces biphasic pulses within the tissues & has an advantage in that it does not cause skin irritation unlike some other electrical techniques [45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The NMES groups in the present study was administered a low frequency electrical stimulation during the recovery period showed a significant recovery of blood lactate and anaerobic performance as compared to control group, which is similar to the results found in previous studies [21,24,26,27,30,[38][39][40][41], although some studies have also reported contrasting findings [21,[42][43][44]. IFT used produces biphasic pulses within the tissues & has an advantage in that it does not cause skin irritation unlike some other electrical techniques [45].…”
Section: Discussionsupporting
confidence: 90%
“…The reasons for the IPC's success in decreasing BLa more than the passive recovery in this study might be due to its ability to mimic the muscle venous pump [39,49]. IPC has a potential role in altered limb circulation, lymphatic flow & general metabolic clearance [30,40,[50][51][52][53]. The results suggest that IPC may be superior option to passive recovery when -inactive'' BLa clearance is desirable (eg.…”
Section: Discussionmentioning
confidence: 98%
“…In this study we chose to use an inflation protocol consisting of target inflation pressures of ~70 mm Hg for each chamber and a duty cycle that included 30 s of compression in each zone followed by a 30 second rest period during which all zones are deflated. We have previously investigated and described this protocol and system [6, 16] and a simple illustration of the compression pattern delivered by the EPC system is presented in Fig 2. 1 h following the conclusion of EPC or sham treatments, participants donated a second muscle biopsy from the left vastus lateralis (termed POST1) using techniques and processing procedures described above.…”
Section: Methodsmentioning
confidence: 99%
“…While it has been posited that EPC can exert localized vasoactive effects [5] and improve post-exercise lactate clearance [6], EPC devices are also putatively analogous to a lower-limb massage which has been shown to decrease exercise-induced inflammatory signaling [7]. Interestingly, investigators have reported that a single 15 min EPC treatment acutely improves flexibility [8] and increases the pressure-to-pain threshold (PPT) in the lower limbs following resistance training [9].…”
Section: Introductionmentioning
confidence: 99%
“…The "leg sleeves" are connected to an automated pneumatic pump at which target inflation pressures for each zone and the duty cycle can be controlled. However, the unit is commercially marketed with preprogrammed defaults for the duty cycle and recommended inflation pressure settings for recovery that we have previously investigated and described (Martin et al 2015b). Therefore, in this study, we chose to use the recovery protocol recommended by the manufacturer with target inflation pressures of ~70 mmHg for each chamber.…”
Section: Treatments: External Pneumatic Compression (Epc) and Shammentioning
confidence: 99%